Modified polyphenyl ether material as well as foamed beads and foamed molded body thereof
By introducing carbonyl-containing crosslinking agents and divalent metal ion crosslinking additives into the polyphenylene ether material, a reversible crosslinking structure is formed, which solves the problem of poor melting fluidity of the polyphenylene ether material during processing, and significantly improves its processing performance and foaming properties.
Patent Information
- Application Number
- CN202311269933.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
Polyphenylene ether resin materials have poor melting fluidity and difficulty in processing during processing, which limits their application in foaming materials.
By introducing a crosslinking agent containing a carbonyl group and a crosslinking additive containing a divalent metal ions into the polyphenylene ether material, a reversible crosslinking structure is formed to improve the processing and mechanical properties of the material.
At room temperature and below the thermal deformation temperature, the modified polyphenylene ether material maintains good mechanical properties; at high temperature, the crosslinked structure is destroyed, significantly improving the material's fluidity and processing properties, and improving the content and foaming properties of the polyphenylene ether.
Smart Images

Figure BDA0004475275390000081 
Figure BDA0004475275390000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical industry, in particular to a modified polyphenylene ether material and its foaming beads and foaming molding. Background Art
[0002] Polyphenylene ether resin is a new type of high-performance thermoplastic resin with a strength of about 70MPa, which is about 3 times that of polyethylene. The elastic modulus is greater than 2000MPa. The material's impact resistance is greater than 430J / m, and the heat deformation temperature is as high as 120°C. The product has good dimensional stability and its creep resistance is the best among the five major engineering plastics. It has high reliability in long-term use, is intrinsically flame retardant, and is a low-smoke, halogen-free, and environmentally friendly flame retardant material.
[0003] The polyphenylene ether resin can be foamed to achieve lightweight and unique functionality, such as heat insulation, sound insulation, cushioning and low dielectric properties. Polyphenylene ether foam beads can expand and bond together during heating, and can be processed into foam products of various shapes and structures, which are widely used in cushioning packaging, building insulation, cold chain logistics, toys and other fields. In addition, due to the excellent heat resistance and dimensional stability of polyphenylene ether foam beads, they have broad application fields in automobiles, new energy batteries, precision instruments and other fields.
[0004] However, high-performance polyphenylene sulfide or polyphenylene ether resin molecules have the disadvantages of strong rigidity, high glass transition temperature, difficulty in orientation, high residual internal stress in the product, poor melt fluidity, and difficulty in processing. These shortcomings undoubtedly limit the application of polyphenylene ether resin materials.
[0005] In order to obtain a polyphenylene ether foamed material having excellent heat resistance and dimensional stability, it is very necessary to modify the polyphenylene ether resin so as to make it suitable as a foaming material.
[0006] CN100587803C states that "in the modified polyphenylene ether resin constituting the modified polyphenylene ether resin foam sheet, the polyphenylene ether component is 15-60% by weight, and the styrene component is 40-85% by weight." This is because if the polyphenylene ether component in the modified polyphenylene ether resin is too little, the heat resistance of the foam sheet will decrease, and if the polyphenylene ether component is too much, a good foam sheet cannot be obtained, and the polyphenylene ether content cannot be greater than 60% by weight.
[0007] In CN102471517B, "the base resin comprises 40wt% to 94wt% polyphenylene ether resin, 5wt% to 20wt% flame retardant and 0.3wt% to 10wt% rubber component, and the remainder is composed of polystyrene resin." Although the content of polyphenylene ether in the claims can be greater than 60%, the maximum content of polyphenylene ether in the provided embodiments is 70%, and the comparative examples with a content of 96wt% and 85wt% have poor foaming effects. In order to improve the foamability, 0.3wt% to 10wt% of rubber component needs to be added.
[0008] CN109054337A provides a formula, preparation method and application of modified polyphenylene ether foam beads. CN110591331A discloses a similar technical solution using "PP-g-MAH, SEBS-g-MAH, PE-g-MAH, EPDM and POE-g-GMA" as compatibilizers. However, although such polymers are often used as compatibilizers, they are incompatible with polyphenylene ether in the system, which greatly weakens the effect of the compatibilizer and leads to deterioration of material properties.
[0009] CN103910966A also provides a method for preparing a foamed polyphenylene ether / polystyrene blend alloy material, which is prepared by using a chemical foaming agent and an extrusion foaming method.
[0010] CN114736505A provides a method for preparing foamed polyphenylene ether polypropylene composite beads and wafer packaging boxes. "The composite beads are composed of a core layer and a skin layer coated on the outside of the core layer, and the skin layer is polypropylene." The performance of the material is improved by coating a layer of polypropylene on the surface, but the preparation of the composite beads is more complicated and requires special equipment.
[0011] CN113136098A provides a modified polyphenylene ether micro-foam material and a preparation method thereof, wherein maleic anhydride modified polyphenylene ether and polyphenylene ether microspheres containing alloy powder are used for blending and modification with polyphenylene ether, thereby improving the fluidity of polyphenylene ether, making it easy to process and shape, while ensuring its mechanical properties; in particular, by irradiating with gamma rays, the main chain of polyphenylene ether is broken, the rigidity of the main chain is improved, and the melt fluidity is further improved. However, maleic anhydride and polyphenylene ether are only physically mixed.
[0012] CN114230845A discloses a high-strength polyphenylene sulfide foam and a preparation and molding method thereof. High-temperature-resistant and high-melt-viscosity PPO is used to improve the viscoelasticity of PPS. Based on HIPS with excellent flexibility, active functional groups such as epoxy groups and acid anhydrides are grafted onto its molecules through a simple and efficient reactive melt processing method to prepare a functionalized HIPS compatibilizer. The good compatibility of HIPS with PPO and the ring-opening reaction of the grafted active functional groups with the thiol groups of the PPS molecules are utilized to form chemical bonding between the components of the blending system, thereby improving its interface compatibility and the flexibility of the molecules. Summary of the invention
[0013] In view of this, the technical problem to be solved by the present invention is to provide a modified polyphenylene ether material and its foamed beads and foamed molded body. The modified polyphenylene ether material has good flowability and processing performance, and the modified polyphenylene ether material has excellent mechanical properties and foaming properties.
[0014] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0015] The invention provides a modified polyphenylene ether material, comprising the following components: polyphenylene ether, a crosslinking agent containing a carbonyl group, and a crosslinking auxiliary agent containing a divalent metal ion.
[0016] The carbonyl oxygen atom in the cross-linking agent containing a carbonyl group is connected to the metal atom in the cross-linking auxiliary agent containing a divalent metal ion to form a reversible cross-linking structure.
[0017] In the present invention, the carbonyl-containing crosslinking agent and the divalent metal ion-containing crosslinking aid form a temperature-responsive reversible crosslinking structure, which greatly improves the processing performance of the modified polyphenylene ether material at high temperature and the mechanical properties of the modified polyphenylene ether material at room temperature and below the heat deformation temperature (HDT).
[0018] When processed at high temperature, the cross-linked structure is destroyed, thereby improving the fluidity and processability of the modified polyphenylene ether material. At the same time, it is preferred to use a low molecular weight cross-linking agent, whose plasticizing effect can greatly increase the content of polyphenylene ether in the material.
[0019] At room temperature and below HDT, the cross-linked structure is stable, so that the modified polyphenylene ether material maintains good mechanical properties.
[0020] The HDT temperature range of the modified polyphenylene ether material of the present invention is 80°C-120°C.
[0021] In the present invention, the normal temperature is 10°C-30°C.
[0022] Preferably, the reversible cross-linked structure is destroyed at a temperature ≥ 200°C.
[0023] Preferably, the mass ratio of the polyphenylene ether to the cross-linking agent containing a carbonyl group is (50-90):(3-40).
[0024] Preferably, the mass ratio of the cross-linking agent containing carbonyl group to the cross-linking auxiliary agent containing divalent metal ions is (3-40): (0.01-5).
[0025] In the present invention, the cross-linking agent containing a carbonyl group is preferably selected from one or more of styrene-acrylic acid copolymer, styrene-maleic acid copolymer, styrene-maleic anhydride copolymer, styrene-maleimide copolymer, styrene-N-phenylmaleimide copolymer, styrene-methacrylic acid copolymer, and styrene-methyl acrylate copolymer. More preferably, it is one or more of styrene-maleic anhydride copolymer, styrene-maleimide copolymer, and styrene-methacrylic acid copolymer.
[0026] In the present invention, the crosslinking aid containing divalent metal ions is preferably selected from one or more of zinc oxide, calcium chloride, zinc chloride, zinc borate, zinc sulfate, calcium sulfate, and magnesium sulfate. More preferably, the crosslinking aid containing divalent metal ions is selected from one or more of zinc oxide, zinc chloride, and zinc borate.
[0027] Preferably, in the present invention, the modified polyphenylene ether material further comprises a flame retardant.
[0028] The addition of flame retardant can improve the flame retardant properties of modified polyphenylene ether materials, so that the flame retardancy measured by the vertical burning test is V0 or V1.
[0029] Preferably, the mass ratio of the flame retardant to the polyphenylene ether is (5-20):(50-90).
[0030] Preferably, in the present invention, the flame retardant is selected from non-halogen flame retardants.
[0031] Preferably, the non-halogen flame retardant is selected from one or more of tricresyl phosphate, triphenyl phosphate, trimethyl phosphate, resorcinol-diphenyl bisphosphate, liquid tetraphenyl bisphenol A diphosphate, and solid tetraphenyl bisphenol A diphosphate; more preferably, the non-halogen flame retardant is selected from one or more of tricresyl phosphate, resorcinol-diphenyl bisphosphate, and solid tetraphenyl bisphenol A diphosphate.
[0032] Preferably, the modified polyphenylene ether material also includes polystyrene. The function of polystyrene is that polystyrene has good compatibility with polyphenylene ether resin and has a low melt viscosity, which can reduce the melt viscosity of polyphenylene ether and improve its processability.
[0033] The polystyrene is preferably ordinary polystyrene or high impact polystyrene.
[0034] In the present invention, the low molecular weight carbonyl-containing crosslinking agent in the modified polyphenylene ether material has good compatibility with polyphenylene ether, and the addition of a crosslinking aid containing divalent metal ions improves the fluidity of polyphenylene ether and reduces the processing difficulty of polyphenylene ether, thereby making the content of polyphenylene ether in the modified polyphenylene ether material higher.
[0035] In some specific embodiments of the present invention, the modified polyphenylene ether material preferably comprises the following components in terms of mass percentage:
[0036] Polyphenylene ether: 50% to 90%;
[0037] Cross-linking agent containing carbonyl group: 3% to 40%;
[0038] Flame retardant: 5% to 20%;
[0039] Cross-linking aid containing divalent metal ions: 0.01% to 5%;
[0040] Polystyrene makes up 100%.
[0041] Furthermore, in the above components, the carbonyl oxygen atom in the crosslinking agent containing carbonyl groups is connected with the metal atom in the crosslinking auxiliary agent containing divalent metal ions to form a reversible crosslinking structure. The polyphenylene ether content in the modified polyphenylene ether material is greatly increased, reaching 90wt%.
[0042] Inorganic nanomaterials and compatibilizers may also be added to the modified polyphenylene ether material.
[0043] The inorganic nanomaterial is preferably talcum powder, SiO 2 , calcium carbonate, wollastonite, sepiolite, and one or more of nano calcium silicate.
[0044] The compatibilizer is preferably one or more of zinc stearate, calcium stearate, pentaerythritol stearate, stearic acid amide, glyceryl monostearate, erucic acid amide, ethylene bis stearic acid amide, and polytetrafluoroethylene.
[0045] The present invention also provides a modified polyphenylene ether foamed bead, which is prepared by melt extrusion, granulation and foaming of the modified polyphenylene ether material.
[0046] The reversible cross-linked structure formed by the cross-linking agent and the cross-linking aid in the modified polyphenylene ether material is only partially destroyed at the foaming temperature (greater than HDT and less than the processing temperature), and the remaining cross-linked structure provides the foaming material with excellent viscoelasticity, greatly improving the foaming property of the material.
[0047] The preparation method of the modified polyphenylene ether foamed beads may specifically be:
[0048] 1) After the above components are uniformly mixed according to the proportion, they are added into a screw extruder for heating and melt extrusion to obtain modified polyphenylene ether material particles;
[0049] 2) melt-extrude the modified polyphenylene ether material particles obtained in step 1) again, and perform underwater pelletization to obtain uniform foaming particles;
[0050] 3) Adding the particles obtained in step 2) into an autoclave, mixing with a supercritical fluid, and foaming at a constant temperature and pressure to prepare modified polyphenylene ether foamed beads.
[0051] The preparation method of the present invention can mix the various components of the modified polyphenylene ether material evenly through multiple extrusions.
[0052] In the above preparation method, the temperature of the two melt extrusions is preferably 200°C-260°C.
[0053] The particle size of the particles in step 2) is preferably 0.3 to 3 mm.
[0054] The expansion ratio of the particles in step 2) is preferably 2 to 20 times.
[0055] The preparation method utilizes the diffusivity and solubility of supercritical fluid to perform gas infiltration dissolution on modified polyphenylene ether material particles, and then releases the pressure and cools down to obtain modified polyphenylene ether foam beads.
[0056] In some specific embodiments of the present invention, the supercritical fluid in step 3) is preferably carbon dioxide or nitrogen.
[0057] The temperature of the gas permeation dissolution is preferably 130°C to 190°C;
[0058] The pressure of the gas permeation dissolution is preferably 5 to 15 MPa.
[0059] The foaming in the above preparation method can also be carried out multiple times to obtain modified polyphenylene ether foamed beads with a larger foaming ratio.
[0060] After the foaming is completed, the modified polyphenylene ether foam beads prepared above are shaped to obtain a foamed body. Specifically, the modified polyphenylene ether foam beads prepared above are placed in a mold, and the foamed body is prepared by heating and in-mold molding.
[0061] The foamed molded body can be a foamed material such as a sheet material and a special-shaped material.
[0062] Between the above-mentioned foaming and plasticization steps, a pressurization treatment may be performed, specifically, pressurizing the foamed beads in an inorganic gas atmosphere so that the bubbles in the foamed beads are given a certain gas pressure, making it easier to foam and mold more evenly.
[0063] The above-mentioned reversible cross-linking structure significantly improves the foaming property of the modified polyphenylene ether material and increases the polyphenylene ether content in the foaming material.
[0064] The HDT of the modified polyphenylene ether foamed material of the present invention is higher than that of the common foamed polyphenylene ether material, and has good molding performance.
[0065] Compared with the prior art, the modified polyphenylene ether material provided by the present invention comprises the following components: polyphenylene ether, a crosslinking agent containing a carbonyl group, and a crosslinking auxiliary agent containing a divalent metal ion; the carbonyl oxygen atom in the crosslinking agent is connected with the metal atom in the crosslinking auxiliary agent to form a reversible crosslinking structure, and the reversible crosslinking structure enables the polyphenylene ether material to have good mechanical properties at room temperature and below the heat deformation temperature (HDT). The reversible crosslinking structure is destroyed during the high-temperature preparation process, so that the flowability and processing performance of the polyphenylene ether in the material are significantly improved. This is of great significance for solving the problems of poor melt flowability and processing difficulties of polyphenylene ether materials, and provides a new idea for improving the foaming performance of polyphenylene ether foaming materials. DETAILED DESCRIPTION
[0066] In order to further illustrate the present invention, a modified polyphenylene ether material, foamed beads and foamed molded body provided by the present invention are described in detail below in conjunction with embodiments.
[0067] Examples 1 to 8
[0068] Step 1: Material modification
[0069] Prepare the raw materials according to Table 1, take polyphenylene ether (LXR045, intrinsic viscosity 43-47dL / g, Bluestar Ruicheng New Materials Co., Ltd.) as the base material, add modified polymer (styrene polymer), compatibilizer, inorganic nanomaterial and related additives (crosslinking agent, flame retardant, crosslinking aid), mix and heat, and extrude to obtain modified polyphenylene ether material;
[0070] Step 2: Underwater pelletizing
[0071] The modified polyphenylene ether material obtained above is added into a high-speed mixer for uniform mixing, and then put into a twin-screw or triple-screw extruder mixing device to melt and extrude the material at high temperature, and then cooperate with an underwater pelletizing device for underwater pelletizing, so that the pellets cut out have uniform particle size, particle size of 1 mm, high roundness of particle shape, and smooth surface;
[0072] Step 3: Foaming
[0073] Supercritical fluid (carbon dioxide, nitrogen), water, etc. are added to the autoclave, the particles cut out underwater are heated to a certain temperature, the temperature and pressure are kept, and the corresponding foamed beads are obtained by gas penetration and dissolution and pressure release.
[0074] Step 4: Preparation of foamed molded body
[0075] The modified polyphenylene ether foam beads are placed in a mold and molded in the mold to obtain a foamed body, and test specimens are prepared according to the test standard requirements. The HDT test results are shown in Table 1.
[0076] The modified polyphenylene ether foam molding was prepared according to the above steps, and the foam particle density, molding properties and HDT of the foam molding were recorded in Table 1.
[0077] Measurement of load heat deformation temperature HDT: A sample with a size of 80 mm × 10 mm × 4 mm was prepared according to method B in GB / T 1634. A load of 0.45 MPa was applied and the temperature was increased from 30°C at a heating rate of 2°C / min. The temperature at which the deflection reached 0.34 mm was evaluated as the HDT.
[0078] Molding performance: A 300 mm × 300 mm × 17 mm flat plate was molded using a molding machine K-68. Samples with no gaps on the surface, where the expanded beads were tightly fused together and in a plate shape were evaluated as o, and samples with gaps on the surface or unable to be molded into a plate shape were evaluated as x.
[0079] Comparative Example 1
[0080] Compared with Example 1, no cross-linking agent and cross-linking aid were added, the melt viscoelasticity was poor during foaming, the obtained foam beads had a low density, and some perforations occurred, resulting in poor molding performance. In addition, the HDT of the molded body was as low as 70°C. The specific data are shown in Table 1.
[0081] Comparative Example 2
[0082] Compared with Example 1, only the cross-linking agent was added without the cross-linking auxiliary agent. The melt viscoelasticity was poor during foaming, resulting in partial perforation, which led to poor molding performance. In addition, the HDT of the molded body was low, at 75°C. The specific data are shown in Table 1.
[0083] Comparative Example 3
[0084] Compared with Example 1, a crosslinking aid is added but no crosslinking agent is added. Due to the high polyphenylene ether content of 70%, the processing performance is poor and it is difficult to foam. The specific data are shown in Table 1.
[0085] Comparative Example 4
[0086] Compared with Example 1, no crosslinking agent and crosslinking aid were added. Due to the high polyphenylene ether content of 90%, it was difficult to obtain good foamed beads. The specific data are shown in Table 1.
[0087] Table 1 Specific experimental data of Examples 1 to 8 and Comparative Examples 1 to 4
[0088]
[0089]
[0090] In summary, the modified polyphenylene ether material of the present invention has a reversible cross-linked structure formed by connecting the carbonyl oxygen atom in the cross-linking agent with the metal atom in the cross-linking aid, so that the polyphenylene ether material has good mechanical properties at room temperature or below HDT. The reversible cross-linked structure is destroyed during the high-temperature preparation process, so that the flowability and processing performance of the polyphenylene ether in the material are significantly improved.
[0091] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A modified polyphenylene ether material, characterized in that: The invention comprises the following components: polyphenylene ether, a cross-linking agent containing a carbonyl group, and a cross-linking auxiliary agent containing a divalent metal ion; The carbonyl oxygen atom in the cross-linking agent containing a carbonyl group is connected with the metal atom in the cross-linking auxiliary agent containing a divalent metal ion to form a reversible cross-linking structure.
2. The modified polyphenylene ether material according to claim 1, characterized in that: The mass ratio of the polyphenylene ether to the cross-linking agent containing a carbonyl group is (50-90): (3-40); The mass ratio of the cross-linking agent containing carbonyl group to the cross-linking auxiliary agent containing divalent metal ions is (3-40): (0.01-5).
3. The modified polyphenylene ether material according to claim 1, characterized in that: The carbonyl-containing crosslinking agent is selected from one or more of styrene-acrylic acid copolymer, styrene-maleic acid copolymer, styrene-maleic anhydride copolymer, styrene-maleimide copolymer, styrene-N-phenylmaleimide copolymer, styrene-methacrylic acid copolymer, and styrene-methyl acrylate copolymer.
4. The modified polyphenylene ether material according to claim 1, characterized in that: The cross-linking auxiliary agent containing divalent metal ions is selected from one or more of zinc oxide, calcium chloride, zinc chloride, zinc borate, zinc sulfate, calcium sulfate, and magnesium sulfate.
5. The modified polyphenylene ether material according to claim 1, characterized in that: The modified polyphenylene ether material also includes a flame retardant; The mass ratio of the flame retardant to the polyphenylene ether is (5-20): (50-90).
6. The modified polyphenylene ether material according to claim 5, characterized in that: The flame retardant is selected from non-halogen flame retardants.
7. The modified polyphenylene ether material according to claim 6, characterized in that: The non-halogen flame retardant is selected from one or more of tricresyl phosphate, triphenyl phosphate, trimethyl phosphate, resorcinol-bis-diphenyl phosphate, liquid tetraphenyl bisphenol A diphosphate, and solid tetraphenyl bisphenol A diphosphate.
8. The modified polyphenylene ether material according to claim 1, characterized in that: The modified polyphenylene ether material also includes polystyrene.
9. A polyphenylene ether foamed bead, characterized in that: The modified polyphenylene ether material according to any one of claims 1 to 8 is prepared by melt extrusion, granulation and foaming.
10. A polyphenylene ether foamed molded body, characterized in that: The polyphenylene ether foamed beads according to claim 9 are placed in a mold, and heated and molded in the mold to obtain a foamed molded body.
Citation Information
Patent Citations
Foam sheet for interior material of automobile and interior material of automobile
CN100587803C
Expandable beads, molded body using the same, and production method for molded body
CN102471517B
Foamed polyphenyl ether / polystyrene blended alloy material and its preparation method
CN103910966A
Modified polyphenyl ether micro-foaming material and preparation method thereof
CN113136098A
High-strength polyphenylene sulfide foam and preparation and forming method thereof
CN114230845A
Cited By
An in-situ fiber-reinforced modified polyphenylene ether foamed beads and its preparation method
CN122563317A